Left atrial strain in neonates with congenital diaphragmatic hernia and length of stay in pediatric intensive care unit - Tydén, Katarina Övermo; Mesas Burgos, Carmen; Jonsson, Baldvin; Nordenstam, Felicia (Frontiers in Pediatrics, 2024)
The role of cardiac left ventricle (LV) dysfunction in children with congenital diaphragmatic hernia (CDH) has gained increasing attention. The hernia allows abdominal mass to enter thorax and subsequently both dislocating and compressing the heart. The pressure on vessels and myocardium alters blood flow and may interfere with normal development of the LV. A dysfunctional LV is concerning and impacts the complex pathophysiology of CDH. Hence, assessing both the systolic and diastolic LV function in the newborn with CDH is important, and it may add value for medical treatment and prognostic factors as length of stay (LOS) in pediatric intensive care unit (PICU). LV strain is considered an early marker of systolic dysfunction used in the pediatric population. Left atrial (LA) strain is an echocardiographic marker of LV diastolic dysfunction used in the adult population. When filling pressure of the LV increases, the strain of the atrial wall is decreased. We hypothesized that reduced LA strain and LV strain are correlated with the LOS in the PICU of newborns with CDH.Methods: This retrospective observational cohort study included data of 55 children born with CDH between 2018 and 2020 and treated at Karolinska University Hospital, Sweden. Overall, 46 parents provided consent. Echocardiograms were performed in 35 children <72 h after birth. The LA reservoir strain (LASr), LV global longitudinal strain, LV dimensions, and direction of blood flow through the patent foramen ovale (PFO) were retrospectively assessed using the echocardiograms.Results: Children with LASr <33% (n=27) had longer stays in the PICU than children with LA strain 33% (n=8) (mean: 20.8 vs. 8.6 days; p<0.002). The LASr was correlated with the LOS in the PICU (correlation coefficient: -0.378; p=0.025). The LV dimension was correlated with the LOS (correlation coefficient: -0.546; p=0.01). However, LV strain was not correlated to LOS. Conclusion: Newborns with CDH and a lower LASr (<33%) had longer stays in the PICU than children with LASr  33%. LASr is a feasible echocardiographic marker of diastolic LV dysfunction in newborns with CDH and may indicate the severity of the condition.